SYNTHESIS AND COORDINATION CHEMISTRY OF A NOVEL BIS(BENZO CROWN-ETHER) SUBSTITUTED CALIX[4]ARENE THAT CAN SIMULTANEOUSLY COMPLEX CATIONS AND ANIONS - Beer, P; Drew, M; Knubley, R; Ogden, M (1995)
New Calix[4]arene compounds substituted at the lower rim by four (L3) or two (L6) benzo-15-crown-5 (2,3,5,6,8,9,11,12-octahydro-1,4,7,10,13-benzopentaoxacyclopentadecine) groups respectively have been prepared. Proton NMR co-ordination studies with sodium and potassium cations in deuteriated acetonitrile revealed that L3 forms L3·5M+ (M+ = Na+ or K+) solution stoichiometric complexes consisting of an alkali-metal cation bound in each of the four crown ether moieties and one occupying the tetraamide lower-rim cavity. Compound L6 complexes K+, Ba2+ and NH4+ exclusively at the crown ether binding sites in a 1:1 intramolecular sandwich stoichiometric fashion. A crystal-structure determination of [KL6][I3] has been carried out. Although neither L3 nor L6 coordinates anions the potassium and ammonium complexes [ZL6]PF6 (Z = K+ or NH4+) form 1:1 complexes with Cl-, NO3-, HSO4- and H2PO4-. Stability constant evaluations have shown that the strongest anion complexes are produced with H2PO4- and HSO4-.